Pinecone 1943 - Georgia State Womans College (Georgia State Womans College, 1943)
THIS YEAR's ANNUAL the Staff of the 1943 Pine Cone has sought to make a permanent record of the life of an average college girl in a wartime world. In spite of the turmoil and strife in which the world has been plunged, each G. S. W. C. student has cherished memories to take with her throughout life. It is, therefore, our purpose to embody in this book the higher ideals and the memories that a student wishes to remember about her college days. May each of us as we go forth pause and reflect upon the privileges offered to us here. We will be able to say with pride that this has truly been an outstanding year.
A year book was published for Valdosta State College from 1925-1977, under the name The Pinecone. From 1981-1987, a yearbook was published called Milestones. Valdosta State University had three names during this period, Georgia State Womans College, 1925-1950; Valdosta State College, 1950-1993; and Valdosta State University 1993-present.
Keywords: yearbook; Americana